CHARACTERISTICS AND CLINICAL FEATURES OF PHACOEMULSIFICATION CATARACT SURGERY PATIENTS IN PASURUAN EYE HOSPITAL IN 2023 - Pradana, Yuda; Sitaresmi Dutaning Sri Pawenang; H. R. Ach. Hadi Soesilo (Faculty of Medicine Universitas Kristen Duta Wacana, 2024)
Background: Cataract is a disease that has become the most common cause of visual impairment in Indonesia. Its incidence in Indonesia is about 210.000 cases/year, while cataract surgery rate is only 80.000 patients/year. One of provinces in Indonesia that has the highest cataract prevalence based on survey results that has been done by Rapid Assessment of Avoidable Blindness (RAAB) in 2014-2016 is East Java. There were 371.599 blindness cases with 81.1% from all the blindness cases caused by cataract. Objective: This study described characteristics and clinical features of phacoemulsification cataract surgery patients in Pasuruan Eye Hospital in 2023. Method: This quantitative research was done by using descriptive observational design and cross-sectional approach. Variable research was taken from medical records in Pasuruan Eye Hospital. Results: There were 55 cataract surgery patients who completed all appointments with an ophthalmologist until D+30 of the surgery. Research results showed that 48 patients (87.2%) obtained good vision after undergoing cataract surgery using the phacoemulsification method. Proportion of cataract events was greater in women (54.5%) than men (45.5%). The most frequent surgical complication after phacoemulsification was corneal edema (23.6%). Conclusion Most cataract surgery results using the phacoemulsification method show good visual acuity. However, there were cataracts that occur at ages less than 50 years. This condition requires action from health services to investigate the factors that influence the occurrence of cataracts at an earlier age.